Regulatory roles of noncoding RNAs in oil palm response to cold stress - Wu, Qiufei; Li, Rui; Zeng, Xianhai; Fu, Dengqiang; Li, Qihong; Li, Zongming; Cao, Hongxing; Li, Xinyu; Liu, Xiaoyu; Zhou, Lixia (Frontiers in Plant Science, 2025)
IntroductionNoncoding RNAs (ncRNAs) are crucial regulators of cellular functions and are actively expressed in different tissues and throughout various stages of development. However, their roles in oil palm (Elaeis guineensis Jacq.) under abiotic stress, particularly cold stress, remain poorly understood.MethodsWe profiled spear leaves across a cold-stress time course (0–8 h at 8°C), and conducted an in-depth transcriptome analysis to explore and characterize differentially expressed genes (DEGs), differentially expressed microRNAs (DEMs), and differentially expressed lncRNAs (DELs) in oil palm subjected to cold stress, aiming to elucidate the regulatory networks among these molecules. We called DE with |log2FC|≥1 (DEGs/DELs: FDR<0.05; DEMs: p<0.05).Results and discussionComparative analysis revealed 1,106 DELs, 638 DEMs and 13,539 DEGs reacting to cold stress relative to control conditions (CK). GO and KEGG enrichment of DEGs and predicted ncRNA targets highlighted carbohydrate/lipid metabolism and secondary-metabolite biosynthesis. Furthermore, the study demonstrated that miR156-zmiR156-z negatively regulated FabF1 in protoplasts, providing targeted functional validation within the inferred network. The findings offer new perspectives on the regulatory role of ncRNAs in oil palm’s response to cold stress and establish a basis for future functional research. Gaining insight into these molecular mechanisms may help improve cold resilience in oil palm, paving the way for the development of more robust cultivars.